The value of geological data, information and knowledge in producing landslide susceptibility maps. - Tsangaratos, P.; Koumantakis, I. (Bulletin of the Geological Society of Greece, 2013)
The paper attempts to illustrate the value of Geological data, information and knowledge in studies that investigate landslide phenomena and how this is reflected in the production of landslide susceptibility maps. In particular, the concepts of data, information, knowledge and wisdom are defined and also the process of converting data into information and information into knowledge. The presented study continuous with a summary that introduces landslide phenomena and the available techniques and methods for identifying and classifying these natural phenomena. It describes the significance of landslide analysis and how this process is essential in order to orient intelligence decisions regarding strategies for regional and urban development. The susceptibility maps that are considered as the outcomes of the over mentioned process, reflects the Geological Knowledge that has been produced by involving expert knowledge and processing data.